2017
DOI: 10.1097/tp.0000000000001369
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Pharmacokinetics of Tacrolimus in Elderly Compared With Younger Recipients in the First 6 Months After Renal Transplantation

Abstract: These data indicate that Eld recipients have a lower TAC clearance and therefore need a lower TAC dose than younger recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
0
14
1
8
Order By: Relevance
“…Older renal transplant recipients have already been shown to exhibit higher TAC concentrations than younger recipients while being exposed to the same dosage. In the studies of Jacobson et al and David‐Neto et al, the authors reported higher TAC‐normalized concentrations for patients of more than 65 years compared to young and middle age patients . Indeed, TAC is highly metabolized and then predominantly eliminated through biliary excretion.…”
Section: Discussionmentioning
confidence: 96%
“…Older renal transplant recipients have already been shown to exhibit higher TAC concentrations than younger recipients while being exposed to the same dosage. In the studies of Jacobson et al and David‐Neto et al, the authors reported higher TAC‐normalized concentrations for patients of more than 65 years compared to young and middle age patients . Indeed, TAC is highly metabolized and then predominantly eliminated through biliary excretion.…”
Section: Discussionmentioning
confidence: 96%
“…Resultados: Envelhecimento e doença renal crônica apresentaram efeito aditivo em reduzir os números de linfócitos T [AdS=1737(1446T [AdS=1737( -1933 vs. IdS=1172(934-1360) vs. AdDRC=1238(847-1599) vs. IdDRC= 718(484-993)cels/mm 3 , DRC p<0,001 e envelhecimento p<0,001], afetando populações memória, naive e reguladoras, mas sem efeito sinérgico. Envelhecimento [Linfócitos T memória central -AdS=6,7 (5)(6)(7)(8)5) vs. IdS=9,2 (6,(7)(8)(9)(10)(11)9) vs. AdDRC=5,9(3,[3][4][5][6][7][8]8) vs. IdDRC= 7,7(5,[2][3][4][5][6][7][8][9][10][11][12]4)%, DRC p=0,39 e envelhecimento p=0,02] e doença renal crônica [Linfócitos T memória efetora -AdS=28,2 (16,3) vs. IdS=31,2 (23,5) vs. AdDRC=34 (25,7) vs. IdDRC= 39,6(27,6)%, DRC p=0,03 e envelhecimento p=0,19] resultaram ...…”
Section: Lista De Abreviaturas Símbolos E Siglasunclassified
“…Tempo TRS (meses) ------32 5) 36 (21-54 Os AdISP eram mais jovens que os dois grupos de idosos (36±7 vs. 65±3, p <0,0001 e vs. 65±3 anos, p <0,0001), enquanto os grupos de idosos não diferiam quanto à idade. Os grupos não diferiam também quanto a gênero, prevalência de hipertensão arterial sistêmica ou diabetes mellitus.…”
Section: Dados Da Terapia Renal Substitutiveunclassified
See 2 more Smart Citations